2016
DOI: 10.1002/j.0022-0337.2016.80.12.tb06228.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Corporate Climate Principles to Dental School Operations

Abstract: Decades of research have shown that organizational climate has the potential to form the basis of workplace operations and impact an organization's performance. Culture is related to climate but is not the same. "Culture" is the broader term, defining how things are done in an organization, while "climate" is a component of culture that describes how people perceive their environment. Climate can be changed but requires substantial effort over time by management and the workforce. Interest has recently grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the relationship between ethical climate, organizational culture, and organizational performance has been investigated, highlighting the mediating role of strategic service management in tax service offices (Zatna et al, 2022). Additionally, research has shown that organizational culture significantly affects employee retention, job satisfaction, and organizational commitment, while climate impacts human resource management, strategy, and performance (Robinson & Reddy, 2016).…”
Section: Organizational Culture Structure and Climatementioning
confidence: 99%
“…Moreover, the relationship between ethical climate, organizational culture, and organizational performance has been investigated, highlighting the mediating role of strategic service management in tax service offices (Zatna et al, 2022). Additionally, research has shown that organizational culture significantly affects employee retention, job satisfaction, and organizational commitment, while climate impacts human resource management, strategy, and performance (Robinson & Reddy, 2016).…”
Section: Organizational Culture Structure and Climatementioning
confidence: 99%
“…Schneider et al defined organizational climate in their review article as "the shared perceptions of and the meaning attached to the policies, practices, and procedures employees experience and the behaviors they observe getting rewarded and that are supported and expected." 8 Robinson and Reddy published an excellent example of an organizational climate study in a dental school in 2016, 9 while McCann and colleagues provided information about their cultural climate study at the Texas A & M College of Dentistry in 2017. 10 Despite these school-specific climate studies, no research so far explored the academic climate in dental schools in the United States and Canada comparatively.…”
Section: Introductionmentioning
confidence: 99%